1983
DOI: 10.1073/pnas.80.18.5749
|View full text |Cite
|
Sign up to set email alerts
|

Critical role played by thyroid hormone in induction of neoplastic transformation by chemical carcinogens in tissue culture.

Abstract: Incubation of primary cultures of hamster embryo cells (HEC) or mouse fibroblasts (C3H/IOTI/2 cells) in media depleted of thyroid hormones does not alter cell growth or survival but renders the cells resistant to neoplastic transformation by benzo [a]pyrene (B[a]P) or N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), carcinogens which yield transformation rates of 10-4_10-2 in media supplemented with triiodothyronine (T3). In C3H/10T'/2 cells, the times of addition or removal of the hormone indicate that T3 exerts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 15 publications
1
17
0
2
Order By: Relevance
“…Thus, erbA gene products probably mediate thyroid hormone induction of tissuespecific genes necessary for differentiation of organs such as brain, heart, pituitary and liver (14)(15)(16)(17). Finally, erbA products may mediate the documented activity ofthyroid hormone as a potentiator of carcinogens in some systems (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, erbA gene products probably mediate thyroid hormone induction of tissuespecific genes necessary for differentiation of organs such as brain, heart, pituitary and liver (14)(15)(16)(17). Finally, erbA products may mediate the documented activity ofthyroid hormone as a potentiator of carcinogens in some systems (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these processes can be manipulated for the c-Ki-ras gene in the C3H/10TY2 cell culture transformation system. Borek et al (21) have shown that thyroid hormone is an important "cofactor" for chemical transformation of C3H/1OTY2 cells. Guernsey and Leuthauser (22) showed that the presence of triiodothyronine in the medium immediately prior to and during exposure to MCA increased the transformation frequency of C3H/1OTY2 cells by as much as 6- 24).…”
Section: Resultsmentioning
confidence: 99%
“…That estrogen may support breast tumor growth nongenomically is now under consideration (Silva & Shupnik, 2007), perhaps involving nuclear ERα insinuated into the plasma membrane or ER-like proteins in the membrane (Levin, 2011). The concept that thyroid hormone may be a growth factor for breast cancer has been advanced by various investigators (Goodman et al, 1980;Borek et al, 1983;Cristofanilli et al, 2005). That thyroid hormone could nongenomically support ER-positive human breast cancer cell proliferation and to be estrogen-like was shown when T 4 caused MAPKdependent specific serine phosphorylation of nuclear ER, mimicking estradiol upon which depended stimulation of proliferation by the iodothyronine.…”
Section: Discussionmentioning
confidence: 99%